Pengaruh Product Quality dan Service Quality Terhadap Customer Loyalty Melalui Customer Satisfaction Sebagai Variabel Mediasi (Studi Pada Pelanggan Mie Gacoan di Kota Semarang) - Muhammad Ainur Rojikin; Bogy Febriatmoko (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the effect of product quality and service quality on customer loyalty of Mie Gacoan in Semarang through customer satisfaction as a mediating variable. A quantitative method was used with an explanatory approach, involving 140 respondents selected through purposive sampling. Data were collected using online questionnaires and analyzed using PLS-SEM with SmartPLS 4.0. The results showed that product quality and service quality had a significant effect on customer loyalty, both directly and indirectly through customer satisfaction as a mediating variable. These findings highlight the importance of maintaining consistent product standards and improving service responsiveness to enhance customer satisfaction and strengthen customer loyalty